Mediação das relações econômicas internacionais privadas - Fonseca, Pedro Paulo Corino da (2007)
The International Law controversy regarding the efficiency of the Judiciary is huge. Looking forward to guarantee a solution to that point, it is was proposed methodologies and techniques focusing dispute settlement resolution. Constantly, dispute settlement resolution of controversies are becoming more and more part of societies, worldwide. By Law, by marketing these new options and also because of the necessity of the parties. In Brazil, there is a preponderant advantage do Arbitration and to Med-Arb . But those are not the best ways of Justice administration. Among the variety of dispute settlement resolution techniques, are: the Mini-Trial; Conciliation; Arbitrational Inspection; summary jury trial, and mediation. Whereas the International experience, Mediation deserves a special attention of study, regarding its results and its logically possible results. Used since millenniums ago, Mediation settles the dubium with much more property and celerity then Judicial or Arbitration Courts, which decisions of who is right or wrong, usually doesn t correspond to the parties necessity. Mediation is considered by doctrine a methodology of multidisciplinary controversy solution, in which the parties relation is discussed to, then, discuss the objective facts. This dissertation proposes an absolutely segregation of Mediation as a family methodology, from Corporate Mediation; pointing propaedeutical reasons to the construction of a Mediation institute as an static Law concept. As proposed by International doctrine, in the end, it is clear the necessity of a Brazilian political incentive to the dispute settlement resolution of controversies. And so on, this dissertation will investigate, under rigid Law concepts, how to generate effective results to Mediation in International Private Economical Relations, in Brazil, regarding Law and Contractual clauses. In such case, there are two major points: (i) the exigency to have Lawyers as Mediators; and (ii) the deontological duty of Lawyers to propose mediation to its clients